Upaya Peningkatan Presentase SDGS Pendidikan Berkualitas Melalui Program Pengenalan Microsoft dan Pembuatan Kalkulator Sederhana - Ahmad Sabiqun Nawa; Akhmadah Maulidiyah; Amanda Nazhira F; Trisnanda Marselina Ariyanto; Yosi Dieta Pratama; Mohammad Idhom (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Education has an important role in improving the quality of human resources in Indonesia. Education is greatly influenced by various factors, such as students, teachers, infrastructure and the environment. As technology develops, the use of technology in education becomes increasingly important. Through a program introducing Microsoft Office (Word, PowerPoint, and Paint) and making simple calculators, this research aims to improve the basic technology and mathematics skills of students at SDN Carangwulung 3. The introduction of Microsoft Office is expected to improve students' ability to use technology, while making simple calculators for make it easier for students to count. This research uses qualitative research methods, with observation, interviews and non-numerical data analysis. The research results show that the program introducing Microsoft Office and making simple calculators can improve students' basic technology and mathematics skills. This service effort emphasizes the importance of using technology in improving the quality of education, as well as efforts to achieve the Sustainable Development Goals (SDGs) in the education sector. Apart from that, this research also shows that there are efforts to increase exposure to SDGs in Carangwulung Village through programs carried out by Group 04 KKNT MBKM UPN "Veteran" East Java.